(untitled) (Architecture Image Studies, 2025)
This research investigates site-specific artistic installations in the form of coral gardens as a medi-um for marine conservation to raise awareness about the critical role of coral reefs in sustaining marine biodiversity and food sources. The artistic approach combines sculptural methods and site-specific installations using recycled, up-cycled, and environmentally friendly materials, which include recycled stones from nearby streams, leftover gravel from construction sites, cockle shells collected from local food vendors, and pH-neutral cement.These materials were carefully selected for their low environmental impact and ability to relate to the project, both the local environment and the communities. This research uses underwater photography surveys and ecological indica-tors to monitor how well the coral grows and how healthy the reef ecosystem is.Through this interdisciplinary approach, the research demonstrates how art and science can work together to inspire environmental stewardship and drive actionable change in marine conservation. By con-necting people with nature, such as coral reefs and marine life, this project highlights the urgency of collective concerted action in protecting our planet through integrating art and science.